Cavitation-Induced Shear Failure Mechanism of Fractured Plugging Zone and Structure Strengthening Method for Lost Circulation Control in High-Temperature and High-Pressure Fractured Gas Reservoirs - Xiaoming Su; Xiaodong Wang; Yuan Yuan; Yun Ren; Wang Gaoming (Geofluids)
The stability of the plugging zone has a great impact on lost circulation control and gas invasion prevention in fractured reservoirs. In this work, the concept of “cavitation-induced shear failure” is put forward based on the analysis of the flow field characteristics, and the failure mechanism is discussed. The strength physical model of a fractured plugging zone is formed based on the analysis of the characteristic parameters of LCMs and the failure mechanism. And then the simulation experiments of cavitation-induced shear failure, gas invasion prevention, pressure bearing, and tight plugging are carried out. The research shows that (1) the fractured plugging zone is a dense granular matter system, and the contact forces and quid bridge force are dominant in its internal; (2) the cavitation-induced shear failure is one of the main failure modes of the plugging zone in a fractured gas reservoir, and the failure process includes three steps: gas diffusion-dilution damage, confluence and carry damage, and displacement dislocation shear failure; (3) the strengthening model of the plugging zone, “rigid bridging+elastoplastic filling+lacing wire of fiber+film-forming seal,” is a better model, and experiments prove that it can form a tight pressure-bearing plugging zone, preventing drill-in fluid loss. The research results provide a theoretical and technical basis for the lost circulation control of fractured gas formations.